Optimization of Liposome Formulations for Enhanced Bioavailability of Hydrophobic Drugs - Merty Adni; Nerty Ambi (Yayasan Adra Karima Hubbi, 2025)
Background: Hydrophobic drugs often face challenges in achieving sufficient bioavailability due to their poor solubility in aqueous environments. Liposomes, with their ability to encapsulate both hydrophilic and hydrophobic compounds, present a promising solution to enhance the bioavailability of these drugs. Optimization of liposome formulations is crucial to maximize their effectiveness in drug delivery. Objective: This study aims to optimize liposome formulations to enhance the bioavailability of hydrophobic drugs. The research focuses on identifying key formulation parameters that influence the encapsulation efficiency, stability, and release profiles of liposome-encapsulated hydrophobic drugs. Methods: Various liposome formulations were prepared using different lipid compositions, cholesterol content, and preparation methods. The hydrophobic drug was encapsulated in the liposomes, and the formulations were characterized for particle size, zeta potential, encapsulation efficiency, and drug release profiles. In vitro studies were conducted to evaluate the stability and release kinetics of the formulations. Additionally, in vivo studies in animal models were performed to assess the bioavailability and therapeutic efficacy of the optimized liposome formulations. Results: The optimized liposome formulation demonstrated a significant increase in encapsulation efficiency and stability compared to initial formulations. Particle size analysis revealed that smaller liposomes with a high cholesterol content exhibited improved stability and prolonged drug release. In vitro and in vivo studies confirmed that the optimized liposomes enhanced the bioavailability of the hydrophobic drug, resulting in higher plasma drug concentrations and improved therapeutic outcomes. Conclusion: Optimization of liposome formulations is essential for enhancing the bioavailability of hydrophobic drugs. The study identified critical formulation parameters that influence the performance of liposome-encapsulated drugs, providing valuable insights for future development. These findings support the potential of optimized liposome formulations to improve the delivery and efficacy of hydrophobic drugs.